Shoreline morphological change prognostic model based on spatiotemporal framework imagery data on the northern coast of Java, Indonesia - Khakhim N.; Kurniawan A.; Pranowo W.S. (Kuwait Journal of Science)
This study focuses on identifying the degree of shoreline changes on the north coast of Java Island (Indonesia), particularly the Batang Regency segment, using multiple data sources: Landsat 9 and 8, Landsat 5 TM, and PlanetScope spanning from 2000 to 2023. The degree of change was obtained by statistically calculating net shoreline movement (NSM), linear regression rate (LRR), and end-point rate (EPR) using the digital shoreline analysis system (DSAS) software. The three rate-of-change statistics were used to calculate the multidecadal shoreline change prediction or projection for the next 10 and 20 years using a Kalman filter-based model with a simple data assimilation technique. Based on these results, NSM indicated that the shoreline experienced a total accretion and erosion of 361.04 and 111.58 m, respectively, from 2000 to 2023. Over these years, the highest accretion rate reached 16.44 m/year (according to LRR) or 15.83 m/year (EPR), while the maximum erosion rate was up to 11.34 m/year (LRR) or 9.43 m/year (EPR). The use of two data sources with different spatial resolutions produces varying statistical values, which depend on the degree of detail and complexity of the data derived from the source imagery. The coastline prognosis model produced with the Kalman filter shows that the entire coastline in Batang Regency will most likely experience an average accretion and erosion of 18.03 and 21.42 m, respectively, in 10 years, while that in the next 20 years will be 26.38 and 33.3 m, respectively. © 2024 The Author(s)